Soil CO2 efflux in a tropical forest in the Central Amazon - Doff, Sotta, Eleneide; Meir, Patrick W.; Malhi, Yadvinder Singh; Nobre, Antônio Donato; Hodnett, Martin G.; Grace, John (Global Change Biology, 2004)
This study investigated the spatial and temporal variation in soil carbon dioxide (CO2) efflux and its relationship with soil temperature, soil moisture and rainfall in a forest near Manaus, Amazonas, Brazil. The mean rate of efflux was 6.45 ± 0.25 SE μmol CO2m-2s-1 at 25.6 ± 0.22 SE°C (5 cm depth) ranging from 4.35 to 9.76 μmol CO2 m-2s-1; diel changes in efflux were correlated with soil temperature (r2 = 0.60). However, the efflux response to the diel cycle in temperature was not always a clear exponential function. During period of low soil water content, temperature in deeper layers had a better relationship with CO2 efflux than with the temperature nearer the soil surface. Soil water content may limit CO2 production during the drying-down period that appeared to be an important factor controlling the efflux rate (r2 = 0.39). On the other hand, during the rewetting period microbial activity may be the main controlling factor, which may quickly induce very high rates of efflux. The CO2 flux chamber was adapted to mimic the effects of rainfall on soil CO2 efflux and the results showed that efflux rates reduced 30% immediately after a rainfall event. Measurements of the CO2 concentration gradient in the soil profile showed a buildup in the concentration of CO2 after rain on the top soil. This higher CO2 concentration developed shortly after rainfall when the soil pores in the upper layers were filled with water, which created a barrier for gas exchange between the soil and the atmosphere. © 2004 Blackwell Publishing Ltd.
Keywords: Carbon Dioxide; Forest Soil; Microbial Activity; Rainfall; Soil Emission; Soil Moisture; Soil Temperature; Spatio-temporal Analysis; Amazonas; Manaus; South America